Tools of a mobile instant messaging application for strengthening the Teaching - learning process of English. (Docentes 2.0 Journal, 2020)
The present study seeks to optimize the use of mobile devices in the learning environment (classroom), using a mobile application for instant messaging for massive use, taking advantage of the sending of information through audio, video, images and text, in order to strengthen the learning of English in the apprentices of a training program, in the Agroindustrial Training Center "La Angostura", of the National Learning Service SENA (Colombia). The focus of this research is of a sequential mixed nature, with emphasis on the qualitative, since the activities carried out with the mobile application in four phases are described. The application through the mobile device is evaluated through the Koole FRAME model and the device capabilities or Quinn 4 C. The results show that English learning can be strengthened, motivates autonomous work, fosters collaborative work and improves digital competence. Finally, mobile learning is characterized because “the student will develop their cognitive abilities through interaction, having as support the technology and the tools it provides” (Gómez, 2016).
Keywords: Mobile learning; mobile application; digital tools; instant messaging